Domestic Regulation and Service Trade Liberalization : a Challenge for the WTO. - Sauve, Pierre (World Bank, 2003)
Trade in services, far more than trade in goods, is affected by a variety of domestic regulations, ranging from qualification and licensing requirements in professional services to pro-competitive regulation in telecommunications services. Experience shows that the quality of regulation strongly influences the consequences of trade liberalization. WTO members have agreed that a central task in the ongoing services negotiations will be to develop a set of rules to ensure that domestic regulations support rather than impede trade liberalization. Since these rules are bound to have a profound imp.